Fluoride Varnish as Root Canal Sealer: A Scanning Electron Microscopy and Bacterial Penetration Study - Parirokh, Masoud; Talebizad, Mohammad; Forghani, Farshid Reza; Haghdoost, Ali Akbar; Asgary, Saeed; Eghbal, Mohammad Jafar; Ghoddusi, Jamileh (Iranian Endodontic Journal, 2014)
Introduction: This study was carried out to evaluate the bacterial leakage of root canal fillings when cavity varnish containing 5% fluoride (Duraflur) was used as root canal sealer. Methods and Materials: Root canals of 88 straight single-rooted teeth were prepared. Eighty teeth were randomly divided into 3 experimental groups (n=20) and two positive and negative control groups of ten each. The roots in group I and II were obturated with gutta-percha and AH-26 sealer using lateral condensation technique. The root canal walls in group II were coated with a layer of varnish before obturation. In group III the canals were obturated with gutta-percha and fluoride varnish as the sealer. Enterococcus faecalis (E. faecalis) was used to determine the bacterial leakage during 90 days. The Kaplan Meier survival analysis was used for assessing the leakage and log rank test was used for pairwise comparison. The rest of eight single rooted teeth were selected for scanning electron microscopy (SEM) evaluation with 5000× magnification. Results: Leakage occurred between 20 to 89 days. Group III showed significantly less bacterial penetration than groups I and II (P=0.001 and P=0.011, respectively). However, there was no significant difference between group I and II (P>0.05). SEM evaluation showed that the varnish had covered all dentinal tubules. Conclusion: The present study showed promising results for the use of fluoride varnish as root canal sealer but further in vitro and in vivo studies are needed.